The Use of Android Smartphone as An Effort to Increase Students’ Creativity in Learning Modern Hair Bun Course at Vocational High School in the Pandemic Era - Pritasari, Octaverina Kecvara; Windayani, Novia Restu; Wilujeng, Biyan Yesi; Dwiyanti, Sri (Journal of Vocational and Career Education, 2021)
Learning modern hair bun styling is quite challenging for Cosmetology students, so it is necessary to use an Android smartphone to facilitate their understanding, creativity, and imagination in order to style the hair buns according to the theme. The limited reference books and modules, as well as the lack of modern hair bun learning media, cause the students' low understanding of this course. It is contrary to the condition of the Cosmetology students of at Vocational High School who must be creative and imaginative during the learning process. The problems that want to be revealed are 1) How is the use of Android smartphone on Modern Hair Bun course? and 2) How is the effectiveness of Android smartphone on Modern Hair Bun course to increase students' creativity? The purpose of this Community Service at Vocational High School in the field of Cosmetology by using Android smartphone is to increase the students’ creativity in learning modern hair bun styling. The method used is Research and Development oriented to product development in Community Service for the students of Cosmetology Department State Vocational High School 8 Surabaya. Based on the validation results from the learning media experts, it was found that the use of Android smartphone in learning Modern Hair Bun Course showed significant results in increasing the Cosmetology students’ creativity.